1994
DOI: 10.1046/j.1471-4159.1994.62031112.x
|View full text |Cite
|
Sign up to set email alerts
|

Typical and Atypical Neuroleptics Induce Alteration in Blood‐Brain Barrier and Brain 59FeCl3 Uptake

Abstract: Long‐term neuroleptic medication of schizophrenic patients induces extrapyramidal motor side effects, of which tardive dyskinesia (TD) is the most severe. The etiology of TD is still obscure. Recently, it was suggested that abnormal iron metabolism may play a crucial role in neuroleptic‐induced dopamine D2 receptor super‐sensitivity. The apparent relationship between neuroleptics and iron is further supported by the increase of iron in the basal ganglia of patients with TD. We now report on the ability of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…APs, at concentrations similar to those measured in the serum of highly dosed patients, are already established to induce gross permeability changes in the BBB; for example its permeability to FeCl3, mannitol and inulin are all enhanced by acute administration of 5µM CPZ (Pardridge et al, 1973;Ben-Shachar et al, 1994), a phenomenon indicative of a BBB breach at a drug concentration similar to that occasionally measured in human serum (3µM, 1000ng/ml; Van Putten et al, 1991), and.…”
Section: Introductionmentioning
confidence: 74%
“…APs, at concentrations similar to those measured in the serum of highly dosed patients, are already established to induce gross permeability changes in the BBB; for example its permeability to FeCl3, mannitol and inulin are all enhanced by acute administration of 5µM CPZ (Pardridge et al, 1973;Ben-Shachar et al, 1994), a phenomenon indicative of a BBB breach at a drug concentration similar to that occasionally measured in human serum (3µM, 1000ng/ml; Van Putten et al, 1991), and.…”
Section: Introductionmentioning
confidence: 74%
“…Moreover, as one of the major sources of sICAM‐1 is activated macrophages, the level of sICAM‐1 in the blood serves as a proxy for an activated immune system . Elevated sICAM‐1 as well as MMP9 levels are also a marker of inflammatory blood–brain barrier (BBB) disturbances .…”
mentioning
confidence: 99%
“…Because the blood-brain barrier blocks cells in the brain from exposure to nonheme iron in the plasma, how well peripheral iron indices correlate with central iron content is unclear. Moreover, the association of central with peripheral iron levels appears to be influenced by multiple factors, including age, iron deficiency, and antipsychotic use (14,15). Whereas some investigators have reported that the quantity of nonheme iron in the human brain is largely independent of body iron stores (6), iron deficiency in rats has been shown to decrease nonheme iron in the brain by more than 40% (16), and a positive correlation (r=0.6) was found between serum and CSF ferritin in individuals with restless legs syndrome (17).…”
mentioning
confidence: 99%